2017
DOI: 10.1002/jcb.26201
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Circular RNA ciRS‐7 Abrogates the Tumor Suppressive Effect of miR‐7 on Gastric Cancer via PTEN/PI3K/AKT Signaling Pathway

Abstract: Gastric cancer (GC) has one of the highest mortality rates of malignancies globally. Currently, ciRS-7, a novel circular RNA, has emerged as a potential sponge for miR-7. However, few studies on ciRS-7 in GC have been performed. In this study, we investigated the clinical significance and function of ciRS-7 in GC. First, the expression levels of ciRS-7 in 102 primary GC tissues and the matched para-carcinoma tissues were evaluated and the clinical relevance was confirmed in an independent validation cohort (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
221
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(225 citation statements)
references
References 21 publications
3
221
0
1
Order By: Relevance
“…Accumulating evidence indicates that circRNAs regulate the cell biological process by acting as miRNA sponges. For example, the most well-known circRNA CDR1as promotes proliferation and invasion of different tumors by blocking miR-7 (Hansen et al, 2013b;Weng et al, 2017;Pan et al, 2018;Zou et al, 2019a). circFAT1 suppresses gastric cancer progression by sponging miR-548g and upregulates RUNX1 tumor suppressor (Fang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that circRNAs regulate the cell biological process by acting as miRNA sponges. For example, the most well-known circRNA CDR1as promotes proliferation and invasion of different tumors by blocking miR-7 (Hansen et al, 2013b;Weng et al, 2017;Pan et al, 2018;Zou et al, 2019a). circFAT1 suppresses gastric cancer progression by sponging miR-548g and upregulates RUNX1 tumor suppressor (Fang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ciRS‐7 was speculated as potential biomarker for diagnosing HCC or NSCLC. Interestingly, ciRS‐7 expressions displayed an inverse correlation with miR‐7 expressions within tumour tissues, and ciRS‐7 has also been verified to directly target miR‐7 within tumour cells 13, 14, 15. Nonetheless, the mechanism underlying the correlation between ciRS‐7 and miR‐7 within NSCLC cells was still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ciRS-7 expressions displayed an inverse correlation with miR-7 expressions within tumour tissues, and ciRS-7 has also been verified to directly target miR-7 within tumour cells. [13][14][15] Nonetheless, the mechanism underlying the correlation between ciRS-7 and miR-7 within NSCLC cells was still far from clear. Furthermore, miR-7 also participated in the pathogenesis that initiated the development of assorted disorders through acting on the downstream pathways.…”
Section: Introductionmentioning
confidence: 99%
“…reported that hsa_circ_001988 expression was significantly reduced in patients with colorectal cancer and closely related to tumor differentiation and neuro-invasion. Yao et al [13]. found that circRNA_100876 was tightly correlated with the survival cycle of patients with non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%